Investigation of the Stability of Plantar Compositions Based on Suspension Polyvinyl Chloride and Ethylene Vinyl Acetate Copolymer to Various Aggressive Environments (Eurasian Journal of Engineering and Technology, 2022)
The article presents the results of a study to determine the stability of plantar compositions based on suspension polyvinyl chloride and ethylene vinyl acetate copolymer to various aggressive media. The durability of samples of plantar compositions during prolonged (2-72 hours) immersion in water, gasoline, diesel fuel, antifreeze, industrial oil, acetone and ethyl acetate was studied. The resistance of plantar materials to natural and artificial aging is also investigated in the work